Characterization of Several Paddy Soil Types in Bogor, West Java, Indonesia - . Kurniati; . Sudarsono; . Suwardi (JOURNAL OF TROPICAL SOILS, 2016)
Paddy soil has different morphology and pedogenic characteristics compared to dry land, due to the influence of inundation during several months in a year. Puddling and drying that occurs in turns (redox cycle) in paddy soil can lead to the formation of concretions or rusty Fe and Mn. The main purpose of this study was to understand the changing of the morphological and chemical properties as a result of changing of the dry land to paddy soil. Besides, the study also aimed to understand plow pan layer formation in Podsolic, Latosol, Regosol, and Andosol soil type. Results showed that content of soil density (bulk density) of dry land ranged from 0.5  to 1.0, while paddy soil is 0.8 to 1.0 (g cm-3).  Bulk density values in all four types of soils increased after the changing. Observation also demonstrated that severity levels of paddy soil is higher than dry land, especially in the second and third soil layers or under the surface of soils. Acidity of dry land was likely to be higher than paddy soil. There were no significant differences in nutrient such as C-organic, P and N. Meanwhile, using dithionite as solvent, paddy soil has higher Fe, Mn, and Al content than that of dry land, and remain the same when extracted with pyrophosphate and oxalate. From the four types of soil observed,the paddy soil showed formation of plow pan layer. This was shown by the soil severity level higher than the topsoil or other layers. Paddy soil had unique properties due to redox reaction, thereby providing soil discoloration i.e darker due to high solubility of Fe, Mn, and Al.Keywords: Concretion of Fe and Mn, paddy soil, pedogenesis, plow pan layer [How to Cite: Kurniati, Sudarsono and Suwardi. 2016. Characterization of Several Paddy Soil Types in Bogor, West Java, Indonesia . J Trop Soils 21:. 27-32. Doi: 10.5400/jts.2016.21.1.27]